The type R settlements in the context of the later prehistory and early history of the Riet River Valley - Humphreys, Anthony J B (Department of Archaeology, 2015)
The main purpose of this study is to examine the structure of Type R settlements on two main levels. First as a pattern existing in a geographical region, the definition of that region and the patterning of settlements within it. The second level is the study of one of the individual settlements. The individual settlements are, in effect, the building blocks or single components of the larger settlement pattern; they represent a "pattern within a pattern". The study, therefore, essentially looks for human behaviour patterns at different levels within a region against the background of any environmental factors which may have influenced or determined those patterns and examines the extent to which those patterns are, as a result, reflections of that environment. The aim of the project is to gain some insight into how man behaved in a limited area, and in a given set of circumstances, as some small contribution to the whole problem of the study of man and his behaviour patterns in the past.